2010
DOI: 10.1002/pros.21321
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of acid ceramidase by a 2‐substituted aminoethanol amide synergistically sensitizes prostate cancer cells to N‐(4‐hydroxyphenyl) retinamide

Abstract: This study shows that 4-HPR cytotoxicity is enhanced in a synergistic fashion by inclusion of the AC inhibitor DM102, by a mechanism that enlists generation of ROS, and thus provides a system to raise 4-HPR therapeutic potential. The role of ceramide however in the cytotoxic response is not clear, as blocking ceramide generation failed to rescue PC-3 cells from 4-HPR/DM102 cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…A promising strategy to enhance intracellular ceramide levels involves targeting proteins that regulate ceramide levels. Examples include the acid ceramidase inhibitor DM102 in prostate and breast cancer cell lines (29), tamoxifen (which acts as a potent inhibitor of ceramide glycosylation) in triple-negative breast cancer (24), and, finally, safingol, an inhibitor of sphingosine kinase with efficacies in colon, breast, ovarian, and cervical cancer models currently enrolled in phase I clinical trials (30,31). Here, we have identified the Bcl-2 family protein Bcl2L13 as a first-in-class inhibitor of CerS activity in cancer, particularly in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…A promising strategy to enhance intracellular ceramide levels involves targeting proteins that regulate ceramide levels. Examples include the acid ceramidase inhibitor DM102 in prostate and breast cancer cell lines (29), tamoxifen (which acts as a potent inhibitor of ceramide glycosylation) in triple-negative breast cancer (24), and, finally, safingol, an inhibitor of sphingosine kinase with efficacies in colon, breast, ovarian, and cervical cancer models currently enrolled in phase I clinical trials (30,31). Here, we have identified the Bcl-2 family protein Bcl2L13 as a first-in-class inhibitor of CerS activity in cancer, particularly in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments showed that inhibition of enzymes responsible for the production of apoptotic sphingolipid species (or in some cases overexpression of opposing enzymes) abrogates the cytotoxicity of the drug, and conversely overexpression of the same enzymes correlated with increased chemotherapeutic sensitivity suggesting that certain sphingolipid species are important for cytotoxicity of the drug [219][220][221]. Some other studies have also shown that therapeutic efficacy of cancer drugs can be significantly enhanced in combination with growth-suppressive sphingolipids such as ceramides and sphingosine [222][223][224]. Therefore, manipulation of sphingolipid metabolism comes forward as a good intervention approach for novel therapies [225].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 96%
“…While the characterization of aberrant, cancer-associated gene expression in tissues obtained for diagnosis versus noncancerous tissues is a prominent arena of research (39), the response of tumors to therapy also represents a critical avenue of investigation (22). Work by this group and others has demonstrated that the ceramide-metabolizing enzyme, acid ceramidase (AC), can play an important role in resistance to anticancer therapies (40)(41)(42)(43)(44)(45)(46)(47), including IR (26,36,48,49). In this report, we evaluated transcriptional activation of AC in PCa cells treated with radiation.…”
Section: Introductionmentioning
confidence: 99%